Impact of Natural Farming Cropping System on Rural Households—Evidence From Solan District of Himachal Pradesh, India - Laishram, Chinglembi; Vashishat, Rohit Kumar; Sharma, Subhash; Rajkumari, Bhavna; Mishra, Neha; Barwal, Parul; Vaidya, Manoj Kumar; Sharma, Ravinder; Chandel, Rajeshwar Singh; Chandel, Ashu; Gupta, Rakesh Kumar; Sharma, Neha (Frontiers in Sustainable Food Systems, 2022)
Natural Farming popular as Zero Budget Natural Farming is an innovative farming approach. It is low inputs based, climate resilient and low cost farming system because all the inputs (Insect repellents, fungicide, pesticide) are made up of natural herbs and locally available inputs thereby reducing the use of artificial fertilizers and industrial pesticides. It is becoming increasingly popular among the smallholder farmers of Himachal Pradesh. Under the Natural Farming system, three to twelve crops are cultivated together on the same area, along with leguminous crops as intercrop in order to ensure that no piece of land is wasted and utilized properly. This paper focuses mainly on the different cropping system of Natural Farming and comparing the economics of natural farming(NF) with conventional farming (CF) systems. Study shows that Farmers adopted five major crop combinations under natural farming system i.e. Vegetables based cropping system (e.g. Tomato+Beans+Cucumber, Cauliflower+Pea+Radish), Vegetables-Cereals based cropping system and other three more cropping systems discussed in this paper. The result indicated that a vegetable based cropping system has 19.68 per cent more net return in Kharif and 24.64 per cent in Rabi season as compared to conventional farming vegetable based mono cropping system. NF maximizes land use and reduces the chance of crop yield loss. NF farming has increased returns and in the vegetable cropping system reduction in cost during kharif was 30.73 percent and 11.88 per cent in rabi season all crop combinations as compared to CF. It is found in study that NF was cost savings from not using chemical fertilizers and pesticides, as well as higher benefit from intercrops.